Legal regulation of the safety of hydraulic structures: analysis of legislation and experience of the Republic of Kazakhstan and foreign states - Teleuyev Г.Б.; Bekturganov А.Е.; Nurmukhankyzy Д. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Scientific research on the issues of safety of hydraulic structures in the practice and legislation of the Republic of Kazakhstan and foreign states is comprehensively studied. In a scientific study, the authors proved that the safety of hydraulic structures is of great importance, along with strategic priorities for the state, such as water safety and environmental safety. Recommendations on improving the national legal system based on the experience of such states as the United States, the member states of the European Union, and Finland in ensuring the safety of hydraulic structures were given. Based on a comparative legal analysis, the authors identified such measures as the importance of a direct legislative act in regulating the activities of hydraulic structures, the effectiveness of a special state body and the categorization of hydraulic structures, and the effectiveness of fixing the limits of responsibility of owners to them. The scientific article was prepared in order to implement the project AP26193915, legal regulation of operation and safety of hydraulic structures in the context of Sustainable Development, funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan.